Positive selection of IL‐33 in adaptive immunity of domestic Chinese goats. Issue 6 (23rd February 2017) - Asif, Akhtar Rasool; Awais, Muhammad; Qadri, Sumayyah; Ahmad, Hafiz Ishfaq; Du, Xiaoyong
Abstract: The identification of the candidate genes that play key role in phenotypic variation in livestock populations can provide new information about evolution and positive selection. IL‐33 (71954) (Interleukin) gene is associated with the increased nematode resistance in small ruminants; however, the role of IL‐33 for the genetic control of different diseases in Chinese goat breeds is poorly described in scientific literature. Therefore, the current investigation was performed for the better understanding of the molecular evolution and the positive selection of single‐nucleotide polymorphism in IL‐33 gene. Fixation Index ( F ST )‐based method was used for the outlier loci determination and found that IL‐33 was present in outlier area with the provisional combined allocation of mean heterozygosity and F ST . Positively selected IL‐33 gene was significantly, that is, p (Simul F ST < sample F ST = 0.98*) present in corresponding positive selection area. Hence, our study provided novel information about the nucleotide variations in IL‐33 gene and found to be nonsynonymous which may helpful for the genetic control of diseases by enhancing the immune system in local Chinese goat breeds as well as in other analyzed vertebrate species. Abstract : Positive selection of IL‐33 gene single‐nucleotide polymorphism and molecular evolution. Hence, our study provided novel information about the nucleotide variations in IL‐33 gene and also found to be nonsynonymous which may change function of gene which plays a crucial role in the genetic control of diseases in local Chinese goat breeds.